2003
DOI: 10.1016/s1472-6483(10)61852-4
|View full text |Cite
|
Sign up to set email alerts
|

Day 3 and day 5 morphological predictors of embryo viability

Abstract: Controlling multiple pregnancies in patients undergoing artificial reproductive procedures requires consideration of single embryo transfers. Therefore, refinements for embryo evaluation are needed that select for the most developmentally competent embryo. The present study was designed to identify day 3 and day 5 morphological predictors of viability following transfers in which the morphology and fate of each embryo was precisely determined. Assessments on day 3 included cell number, and the extent of fragme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
82
1
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 158 publications
(88 citation statements)
references
References 42 publications
2
82
1
2
Order By: Relevance
“…than with blastocysts, the patients in the cleavage stage group not only had more embryos transferred per cycle but were also younger than those in the blastocyst transfer group [3]. On the other hand, a number of recent studies have shown significantly higher pregnancy and implantation rates in blastocysts compared to cleavage stage embryo transfers [4][5][6][7][8]. The Cochrane review of 12 randomized controlled trials demonstrated that live birth rates can be optimized by performing blastocyst transfer compared to cleavage stage embryo transfers [9].…”
Section: Introductionmentioning
confidence: 99%
“…than with blastocysts, the patients in the cleavage stage group not only had more embryos transferred per cycle but were also younger than those in the blastocyst transfer group [3]. On the other hand, a number of recent studies have shown significantly higher pregnancy and implantation rates in blastocysts compared to cleavage stage embryo transfers [4][5][6][7][8]. The Cochrane review of 12 randomized controlled trials demonstrated that live birth rates can be optimized by performing blastocyst transfer compared to cleavage stage embryo transfers [9].…”
Section: Introductionmentioning
confidence: 99%
“…Gametes and embryos were maintained at 37°C in a humidified atmosphere of 5 % CO 2 in air as previously described [18,26]. Oocytes were either inseminated within 4-6 h of retrieval or injected 3-5 h after retrieval.…”
Section: Laboratory Protocolsmentioning
confidence: 99%
“…The fertilization check was performed 16-18 h after insemination or ICSI and zygotes having two pronuclei were cultured individually in 25 μl microdrops of Global medium (IVFOnline, Guelph, Ontario, Canada) supplemented with 5 % human serum albumin. Embryo morphology was assessed on day 3 between 66 and 69 h post-insemination/ICSI using standard criteria of number of blastomeres and extent of fragmentation and blastomere asymmetry [9,18]. Fragmentation scores of 0 through 4 were assigned to each embryo, where scores correlated with 0, 1-9, 10-25, 26-50 % or >50 % fragmentation, respectively.…”
Section: Laboratory Protocolsmentioning
confidence: 99%
See 2 more Smart Citations